Conjugated linoliec acids : Synthesis in ruminant animal tissues and their effects on human health - AKRAIM, F. (Al-Mukhtar Journal of Sciences, 2011)
Conjugated linoleic acids represent a group of positional and geometric isomers of linoleic acid cis-9,cis-12C18:2. Ruminant products (meat and milk) are the major source of conjugated linoliec acids due to ruminal biohydrogenation. The cis-9,trans-11C18:2 isomer represent 80-90% of total conjugated linoleic acids. Endogenous synthesis in mammary tissue account for large proportion of cis-9,trans-11C18:2 in milk. Proportion of trans-10,cis-12C18:2 increase under certain dietary conditions. These two isomers exhibit some interesting properties related to human health. The biological properties include limiting the induction and development of malignant tumors, stimulation of immune system and promote growth, lowering blood cholesterol and lowering the body fat mass. Ruminant products rich in these isomers can be considered as functional foods and so the image of these products for consumers can be improved.